Myocardial Work Efficiency, A Novel Measure of Myocardial Dysfunction, Is Reduced in COVID-19 Patients and Associated With In-Hospital Mortality - Minhas, Anum S.; Gilotra, Nisha A.; Goerlich, Erin; Metkus, Thomas; Garibaldi, Brian T.; Sharma, Garima; Bavaro, Nicole; Phillip, Susan; Michos, Erin D.; Hays, Allison G. (Frontiers in Cardiovascular Medicine, 2021)
Background: Although troponin elevation is common in COVID-19, the extent of myocardial dysfunction and its contributors to dysfunction are less well-characterized. We aimed to determine the prevalence of subclinical myocardial dysfunction and its association with mortality using speckle tracking echocardiography (STE), specifically global longitudinal strain (GLS) and myocardial work efficiency (MWE). We also tested the hypothesis that reduced myocardial function was associated with increased systemic inflammation in COVID-19. Methods and Results: We conducted a retrospective study of hospitalized COVID-19 patients undergoing echocardiography (n = 136), of whom 83 and 75 had GLS (abnormal >−16%) and MWE (abnormal <95%) assessed, respectively. We performed adjusted logistic regression to examine associations of GLS and MWE with in-hospital mortality. Patients were mean 62 ± 14 years old (58% men). While 81% had normal left ventricular ejection fraction (LVEF), prevalence of myocardial dysfunction was high by STE; [39/83 (47%) had abnormal GLS; 59/75 (79%) had abnormal MWE]. Higher MWE was associated with lower in-hospital mortality in unadjusted [OR 0.92 (95% CI 0.85–0.99); p = 0.048] and adjusted models [aOR 0.87 (95% CI 0.78–0.97); p = 0.009]. In addition, increased systemic inflammation measured by interleukin-6 level was associated with reduced MWE. Conclusions: Subclinical myocardial dysfunction is common in COVID-19 patients with clinical echocardiograms, even in those with normal LVEF. Reduced MWE is associated with higher interleukin-6 levels and increased in-hospital mortality. Non-invasive STE represents a readily available method to rapidly evaluate myocardial dysfunction in COVID-19 patients and can play an important role in risk stratification.